Phase Tailoring of Ruddlesden–Popper Perovskite at Fixed Large Spacer Cation Ratio. Issue 43 (4th April 2021) - Guo, Jia; Shi, Zejiao; Xia, Junmin; Wang, Kaiyang; Wei, Qi; Liang, Chao; Zhao, Dandan; Zhang, Zhipeng; Chen, Shula; Liu, Tanghao; Mei, Shiliang; Hui, Wei; et al.
Abstract: Ruddlesden–Popper (RP) metal halide perovskites are considered as promising optoelectronic materials due to their good environmental stability and desirable optoelectronic properties. However, the phase composition and ordering in the deposited film, with a fixed ratio of large organic spacer cation in the precursor solution, are hard to be further tailored for specific optoelectronic applications. Herein, it is shown that even with a fixed spacer cation ratio, the phase composition and ordering can still be largely regulated by utilizing different crystallization kinetics of various cations with the inorganic octahedral lead halide. By using two different short cations to compete with the large spacer cation, the phase composition can be continuously tailored from thin multiple quantum wells (MQWs) dominated to 3D perovskite dominated. The phase ordering can be reversed from small n phases' prior to large n phases' prior near the substrate. Finally, with the same amount of large spacer cation protection, the perovskite can be tailored for both high‐performance electroluminescence and photovoltaics with favorable energetic landscape for the corresponding desired first‐order excitonic recombination and second‐order free electron–hole recombination, respectively. This exploration substantially contributes to the understanding of precise phase engineering in RP perovskite and may provide a new insight into the design of multiple functional devices. Abstract : Herein, it is shown that even with a fixed spacer cation ratio, the phase composition and ordering of the deposited Ruddlesden–Popper (RP) perovskite films can still be regulated by utilizing different crystallization kinetics of various short cations with the inorganic octahedral lead halide. Moreover, the favorable phase composition for the function of light‐emitting diodes and solar cells is investigated.